Interaction of Acupuncture and Electroacupuncture on the Pharmacokinetics of Aspirin and the Effect of Brain Blood Flow in Rats - Wu, Ming-Tsang (Hindawi Publishing Corporation, 2013)
Acupuncture and electroacupuncture have been used to improve the brain and motor functions of poststroke patients, and aspirin is used for the prevention of stroke recurrence. Our hypothesis is that acupuncture and electroacupuncture treatments may interact with aspirin in terms of pharmacokinetics via affecting the brain blood flow. The aim of this study is to investigate the potential interactions of acupuncture and electroacupuncture on the pharmacokinetics of aspirin. The effects of acupuncture treatments on brain blood flow were measured by the laser Doppler blood flow imager. The parallel pharmacokinetic study design included three groups: control, acupuncture, and electroacupuncture groups. Two acupoints, namely, Quchi (LI 11) and Zusanli (ST 36), were needled and stimulated electronically in anaesthetized rats. The concentrations of aspirin and its metabolite, salicylic acid were determined by microdialysis and HPLC analysis after aspirin administration (30 mg/kg, i.v.). The brain blood flow responded to electroacupuncture treatments, but the pharmacokinetic parameters of aspirin and salicylic acid in blood and brain were not significantly changed by acupuncture and electroacupuncture treatments. This study may, in part, offer some evidence to support the contention that there is no significant interaction for the combination of aspirin with acupuncture or electroacupuncture.